MIF mediates bladder pain, not inflammation, in cyclophosphamide cystitis. Issue 1 (March 2019) - Ma, Fei; Kouzoukas, Dimitrios E.; Meyer-Siegler, Katherine L.; Hunt, David E.; Leng, Lin; Bucala, Richard; Vera, Pedro L.
Highlights: MIF mediates bladder pain but not bladder inflammation induced by CYP. ISO-1 blocks CYP induced bladder inflammation independent of MIF. MIF may mediate bladder pain by promoting bladder ERK phosphorylation. Abstract: Macrophage migration inhibitory factor (MIF), a proinflammatory mediator, is recognized as a player in inflammatory and neuropathic pain. Cyclophosphamide (CYP) results in bladder inflammation and pain and it's a frequently used animal model of interstitial cystitis/bladder pain syndrome (IC/BPS). Because pretreatment with a MIF inhibitor (ISO-1) prevented both CYP-induced bladder pain and inflammation we used genetic MIF knockout (KO) mice to further investigate MIF's role in CYP-induced bladder pain and inflammation. Abdominal mechanical threshold measured bladder pain induced by CYP in wild type (WT) and MIF KO mice at several time points (0–48 h). End-point (48 h) changes in micturition parameters and histological signs of bladder inflammation were also evaluated. Abdominal mechanical hypersensitivity developed within 4 h after CYP injection (and lasted for the entire observation period: 48 h) in WT mice. MIF KO mice, on the other hand, did not develop abdominal mechanical hypersensitivity suggesting that MIF is a pivotal molecule in mediating CYP-induced bladder pain. Both WT and MIF KO mice treated with CYP showed histological signs of marked bladder inflammation and showed a significant decrease in micturition volume and increase in frequency. Since both changes were blocked in MIF KO mice by pretreatment with a MIF inhibitor (ISO-1) it is likely these are non-specific effects of ISO-1. MIF mediates CYP-induced bladder pain but not CYP-induced bladder inflammation. The locus of effect (bladder) or central (spinal) for MIF mediation of bladder pain remains to be determined.